Patients concerns about spinal surgery in Hafr Al Batin, Saudi Arabia - Mohammed, Zaheer Ahmed (J Family Med Prim Care, 2020)
BACKGROUND: The aim of the research to study the concerns about spine surgery in patients who attending to neurosurgery clinic in Central Hospital and King Khalid General Hospital in hafar Al-Batin. OBJECTIVE: The objective is to determine the concern of patients about spine surgery and to detect the reasons of rejection of the surgery with tying to compare the concerns with the social factors and to know the source of their knowledge. MATERIAL AND METHOD: A cross-sectional study on sample of 91 from the patients who attending neurosurgery clinic who could be suffering from any spinal diseases such as tumors, degenerative, and trauma. A standardized survey questionnaire distributed manually and responses were collected and analyzed. RESULTS: The majority of the survey respondents were suffering from trauma (48.4%). The satisfaction rate among persons undergone spine surgery was 20.9%. A negative correlation between age and level of education; rejection of spine surgery or exploring for alternative treatment because of risk of surgery was observed. The patient feedback revealed that if advised for spine operation was 46.2% will accept, 29.7% will delay surgery and looking to alternatives, while 23.1% will reject because of concerns. CONCLUSION: It is recommended that awareness campaigns are required about the importance of spine surgery and to provide the correct information about the complications of spine surgery and finally give more attention to the correct diagnosis.